High-density tungsten-nickel-copper alloy material and manufacturing method thereof
By adding synergistic agent and modification liquid to the tungsten nickel copper alloy material to coordinate and interface modification, the problem of poor density of existing materials is solved, and the coordinated improvement of strength performance, wear resistance and density is achieved, and the efficiency of the product is improved.
Patent Information
- Application Number
- CN202411871148.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-05-02
AI Technical Summary
The existing tungsten nickel copper alloy materials have poor density, and their strength and wear resistance are difficult to improve in coordination with density, which limits the efficiency of the product.
Tungsten, nickel and copper powder are used as matrix materials, and the collaborative and interface modification are added to optimize material performance. The specific method includes the step of preparing a modified liquid and a synergist, and obtaining the final high-density tungsten nickel copper alloy material by stirring and other treatment methods.
The high density, strength and wear resistance of tungsten nickel copper alloy materials have been achieved, and the efficiency of product usage is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy materials, and in particular to a high-density tungsten-nickel-copper alloy material and a manufacturing method thereof. Background Art
[0002] Alloy is a mixture with metallic properties synthesized by two or more metals and metals or non-metals through a certain method. It is generally obtained by melting into a uniform liquid and solidifying. According to the number of constituent elements, it can be divided into binary alloys, ternary alloys and multi-element alloys. Two or more metals are uniformly fused together through a certain process to form an alloy, such as copper and zinc to form brass, copper and tin to form bronze, copper and nickel to form white copper, and stainless steel is all alloys containing metals such as chromium, nickel and titanium.
[0003] The existing tungsten-nickel-copper alloy has poor density. At the same time, the strength and wear resistance of the product are difficult to coordinate and improve with the density, which limits the use efficiency of the product. Based on this, the present invention further improves it. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a high-density tungsten-nickel-copper alloy material and a manufacturing method thereof to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a high-density tungsten-nickel-copper alloy material, which comprises tungsten, nickel, copper powder, a modifying liquid and a synergist; wherein the mass ratio of tungsten, nickel, copper powder, the modifying liquid and the synergist is (3-5): (1-3): (5-9): (12-14): 1.
[0006] Preferably, the preparation method of the modified liquid is: S1: adding 2-4 parts of nano-silica sol and 1-3 parts of carboxymethyl cellulose to 4-7 parts of lanthanum nitrate solution, and then adding 1-2 parts of dopamine hydrochloride solution, stirring and mixing thoroughly to obtain a treating agent; S2: irradiating the yttrium oxide powder in a proton irradiation box, and obtaining irradiated yttrium oxide powder after the irradiation is completed; S3: stirring the irradiated yttrium oxide and the treatment agent in a weight ratio of 5:2 at a stirring speed of 300 r / min for 2 hours, washing with water and drying after the stirring is completed to obtain a yttrium modifier; S4: 2-4 parts of silane coupling agent KH560, 1-3 parts of urea, 2-5 parts of 6% by mass dodecylbenzenesulfonic acid solution and 2-5 parts of yttrium modifier are fully mixed to obtain a modified solution.
[0007] Preferably, the mass fraction of the lanthanum nitrate solution is 2-5%; the mass fraction of the dopamine hydrochloride solution is 2-5%.
[0008] Preferably, the irradiation power of the irradiation treatment is 350-400W, and the irradiation time is 20-30min.
[0009] Preferably, the preparation method of the synergist is: S11: immersing the aluminum borate whisker into a sufficient amount of zinc sulfate solution, then washing and drying; S12: 2-4 parts of stearic acid, 1-3 parts of silane coupling agent KH550, 3-6 parts of sodium lignin sulfonate solution and 1-2 parts of nano-graphene are fully mixed to obtain a conditioning solution; S13: Stirring and adjusting the dried aluminum borate whiskers and the adjusting liquid in a weight ratio of 2:5, and after the stirring is completed, washing, filtering, and drying to obtain a synergist.
[0010] Preferably, the mass fraction of the zinc sulfate solution is 5-8%; the mass fraction of the sodium lignin sulfonate solution is 6-9%.
[0011] Preferably, the stirring temperature of the stirring and regulating treatment is 55-60° C., the stirring time is 35-45 min, and the stirring speed is 450-500 r / min.
[0012] Preferably, the immersion power for full immersion is 350-400W, and the immersion time is 20-30min.
[0013] A method for manufacturing a high-density tungsten-nickel-copper alloy material comprises the following steps: fully mixing tungsten, nickel, copper powder, a modifying liquid and a synergist, washing, filtering and drying to obtain the high-density tungsten-nickel-copper alloy material.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The tungsten-nickel-copper alloy material of the present invention adopts tungsten, nickel and copper powder as matrix materials, and performs synergistic coordination by adding synergists, and then performs interface modification on the raw materials by using a modifying liquid to optimize the performance effect of the product. The synergist and the modifying liquid are coordinated and synergistically coordinated, and the strength performance, wear resistance and density of the product are coordinated and improved, and the performance effect of the product is coordinated and improved. DETAILED DESCRIPTION
[0015] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] A high-density tungsten-nickel-copper alloy material of this embodiment includes tungsten, nickel, copper powder, a modifying liquid and a synergist; wherein the mass ratio of tungsten, nickel, copper powder, modifying liquid and synergist is (3-5): (1-3): (5-9): (12-14): 1.
[0017] The preparation method of the modified liquid of this embodiment is: S1: adding 2-4 parts of nano-silica sol and 1-3 parts of carboxymethyl cellulose to 4-7 parts of lanthanum nitrate solution, and then adding 1-2 parts of dopamine hydrochloride solution, stirring and mixing thoroughly to obtain a treating agent; S2: irradiating the yttrium oxide powder in a proton irradiation box, and obtaining irradiated yttrium oxide powder after the irradiation is completed; S3: stirring the irradiated yttrium oxide and the treatment agent in a weight ratio of 5:2 at a stirring speed of 300 r / min for 2 hours, washing with water and drying after the stirring is completed to obtain a yttrium modifier; S4: 2-4 parts of silane coupling agent KH560, 1-3 parts of urea, 2-5 parts of 6% by mass dodecylbenzenesulfonic acid solution and 2-5 parts of yttrium modifier are fully mixed to obtain a modified solution.
[0018] The mass fraction of the lanthanum nitrate solution in this embodiment is 2-5%; the mass fraction of the dopamine hydrochloride solution is 2-5%.
[0019] The irradiation power of the irradiation treatment in this embodiment is 350-400W, and the irradiation time is 20-30min.
[0020] The preparation method of the synergist of this embodiment is: S11: immersing the aluminum borate whisker into a sufficient amount of zinc sulfate solution, then washing and drying; S12: 2-4 parts of stearic acid, 1-3 parts of silane coupling agent KH550, 3-6 parts of sodium lignin sulfonate solution and 1-2 parts of nano-graphene are fully mixed to obtain a conditioning solution; S13: Stirring and adjusting the dried aluminum borate whiskers and the adjusting liquid in a weight ratio of 2:5, and after the stirring is completed, washing, filtering, and drying to obtain a synergist.
[0021] The mass fraction of the zinc sulfate solution in this embodiment is 5-8%; the mass fraction of the sodium lignin sulfonate solution is 6-9%.
[0022] The stirring temperature of the stirring adjustment process in this embodiment is 55-60° C., the stirring time is 35-45 min, and the stirring speed is 450-500 r / min.
[0023] The immersion power for full immersion in this embodiment is 350-400W, and the immersion time is 20-30min.
[0024] A method for manufacturing a high-density tungsten-nickel-copper alloy material in this embodiment includes the following steps: fully mixing tungsten, nickel, copper powder, modifying liquid and synergist, washing, filtering and drying to obtain a high-density tungsten-nickel-copper alloy material.
[0025] Example 1. A high-density tungsten-nickel-copper alloy material of this embodiment includes tungsten, nickel, copper powder, a modifying liquid and a synergist; wherein the mass ratio of tungsten, nickel, copper powder, the modifying liquid and the synergist is 3:1:5:12:1.
[0026] The preparation method of the modified liquid of this embodiment is: S1: Add 2 parts of nano-silica sol and 1 part of carboxymethyl cellulose to 4 parts of lanthanum nitrate solution, then add 1 part of dopamine hydrochloride solution, stir and mix thoroughly to obtain a treatment agent; S2: irradiating the yttrium oxide powder in a proton irradiation box, and obtaining irradiated yttrium oxide powder after the irradiation is completed; S3: stirring the irradiated yttrium oxide and the treatment agent in a weight ratio of 5:2 at a stirring speed of 300 r / min for 2 hours, washing with water and drying after the stirring is completed to obtain a yttrium modifier; S4: 2 parts of silane coupling agent KH560, 1 part of urea, 2 parts of 6% by mass dodecylbenzenesulfonic acid solution and 2 parts of yttrium modifier are fully mixed to obtain a modified solution.
[0027] The mass fraction of the lanthanum nitrate solution in this embodiment is 2%; the mass fraction of the dopamine hydrochloride solution is 2%.
[0028] The irradiation power of the irradiation treatment in this embodiment is 350W, and the irradiation time is 20 minutes.
[0029] The preparation method of the synergist of this embodiment is: S11: immersing the aluminum borate whisker into a sufficient amount of zinc sulfate solution, then washing and drying; S12: 2 parts of stearic acid, 1 part of silane coupling agent KH550, 3 parts of sodium lignin sulfonate solution and 1 part of nano-graphene are fully mixed to obtain a conditioning solution; S13: Stirring and adjusting the dried aluminum borate whiskers and the adjusting liquid in a weight ratio of 2:5, and after the stirring is completed, washing, filtering, and drying to obtain a synergist.
[0030] The mass fraction of the zinc sulfate solution in this embodiment is 5%; the mass fraction of the sodium lignin sulfonate solution is 6%.
[0031] The stirring temperature of the stirring adjustment process in this embodiment is 55° C., the stirring time is 35 min, and the stirring speed is 450 r / min.
[0032] The immersion power for full immersion in this embodiment is 350 W, and the immersion time is 20 min.
[0033] A method for manufacturing a high-density tungsten-nickel-copper alloy material in this embodiment includes the following steps: fully mixing tungsten, nickel, copper powder, modifying liquid and synergist, washing, filtering and drying to obtain a high-density tungsten-nickel-copper alloy material.
[0034] Example 2. A high-density tungsten-nickel-copper alloy material of this embodiment includes tungsten, nickel, copper powder, a modifying liquid and a synergist; wherein the mass ratio of tungsten, nickel, copper powder, the modifying liquid and the synergist is 5:3:9:14:1.
[0035] The preparation method of the modified liquid of this embodiment is: S1: Add 4 parts of nano-silica sol and 3 parts of carboxymethyl cellulose to 7 parts of lanthanum nitrate solution, then add 2 parts of dopamine hydrochloride solution, stir and mix thoroughly to obtain a treatment agent; S2: irradiating the yttrium oxide powder in a proton irradiation box, and obtaining irradiated yttrium oxide powder after the irradiation is completed; S3: stirring the irradiated yttrium oxide and the treatment agent in a weight ratio of 5:2 at a stirring speed of 300 r / min for 2 hours, washing with water and drying after the stirring is completed to obtain a yttrium modifier; S4: 4 parts of silane coupling agent KH560, 3 parts of urea, 5 parts of 6% by mass dodecylbenzenesulfonic acid solution and 5 parts of yttrium modifier are fully mixed to obtain a modified solution.
[0036] The mass fraction of the lanthanum nitrate solution in this embodiment is 5%; the mass fraction of the dopamine hydrochloride solution is 5%.
[0037] The irradiation power of the irradiation treatment in this embodiment is 400W, and the irradiation time is 30 minutes.
[0038] The preparation method of the synergist of this embodiment is: S11: immersing the aluminum borate whisker into a sufficient amount of zinc sulfate solution, then washing and drying; S12: 4 parts of stearic acid, 3 parts of silane coupling agent KH550, 6 parts of sodium lignin sulfonate solution, and 2 parts of nano-graphene are fully mixed to obtain a conditioning solution; S13: Stirring and adjusting the dried aluminum borate whiskers and the adjusting liquid in a weight ratio of 2:5, and after the stirring is completed, washing, filtering, and drying to obtain a synergist.
[0039] The mass fraction of the zinc sulfate solution in this embodiment is 8%; the mass fraction of the sodium lignin sulfonate solution is 9%.
[0040] The stirring temperature of the stirring adjustment process in this embodiment is 60° C., the stirring time is 45 min, and the stirring speed is 500 r / min.
[0041] The immersion power for full immersion in this embodiment is 400 W, and the immersion time is 30 min.
[0042] A method for manufacturing a high-density tungsten-nickel-copper alloy material in this embodiment includes the following steps: fully mixing tungsten, nickel, copper powder, modifying liquid and synergist, washing, filtering and drying to obtain a high-density tungsten-nickel-copper alloy material.
[0043] Example 3. A high-density tungsten-nickel-copper alloy material of this embodiment includes tungsten, nickel, copper powder, a modifying liquid and a synergist; wherein the mass ratio of tungsten, nickel, copper powder, the modifying liquid and the synergist is 4:2:6:13:1.
[0044] The preparation method of the modified liquid of this embodiment is: S1: Add 3 parts of nano-silica sol and 2 parts of carboxymethyl cellulose to 5.5 parts of lanthanum nitrate solution, then add 1.5 parts of dopamine hydrochloride solution, stir and mix thoroughly to obtain a treatment agent; S2: irradiating the yttrium oxide powder in a proton irradiation box, and obtaining irradiated yttrium oxide powder after the irradiation is completed; S3: stirring the irradiated yttrium oxide and the treatment agent in a weight ratio of 5:2 at a stirring speed of 300 r / min for 2 hours, washing with water and drying after the stirring is completed to obtain a yttrium modifier; S4: 3 parts of silane coupling agent KH560, 2 parts of urea, 3.5 parts of 6% by mass dodecylbenzenesulfonic acid solution and 3.5 parts of yttrium modifier are fully mixed to obtain a modified solution.
[0045] The mass fraction of the lanthanum nitrate solution in this embodiment is 3.5%; the mass fraction of the dopamine hydrochloride solution is 3.5%.
[0046] The irradiation power of the irradiation treatment in this embodiment is 370W, and the irradiation time is 25 minutes.
[0047] The preparation method of the synergist of this embodiment is: S11: immersing the aluminum borate whisker into a sufficient amount of zinc sulfate solution, then washing and drying; S12: 3 parts of stearic acid, 2 parts of silane coupling agent KH550, 4.5 parts of sodium lignin sulfonate solution and 1.5 parts of nano-graphene are fully mixed to obtain a conditioning solution; S13: Stirring and adjusting the dried aluminum borate whiskers and the adjusting liquid in a weight ratio of 2:5, and after the stirring is completed, washing, filtering, and drying to obtain a synergist.
[0048] The mass fraction of the zinc sulfate solution in this embodiment is 6.5%; the mass fraction of the sodium lignin sulfonate solution is 7.5%.
[0049] The stirring temperature of the stirring adjustment process in this embodiment is 57.5° C., the stirring time is 40 min, and the stirring speed is 470 r / min.
[0050] The immersion power for full immersion in this embodiment is 375W, and the immersion time is 25 minutes.
[0051] A method for manufacturing a high-density tungsten-nickel-copper alloy material in this embodiment includes the following steps: fully mixing tungsten, nickel, copper powder, modifying liquid and synergist, washing, filtering and drying to obtain a high-density tungsten-nickel-copper alloy material.
[0052] Comparative Example 1. The difference from Example 3 is that no modifying liquid is added.
[0053] Comparative Example 2. The difference from Example 3 is that no yttrium modifier is added to the modified solution.
[0054] Comparative Example 3. The difference from Example 3 is that no treating agent is used in the preparation of the yttrium modifier.
[0055] Comparative Example 4. The difference from Example 3 is that no lanthanum nitrate solution or dopamine hydrochloride solution is used in the treating agent.
[0056] Comparative Example 5. The difference from Example 3 is that no synergist is added.
[0057] Comparative Example 6. The difference from Example 3 is that no conditioning solution is used in the synergist.
[0058] The product performance tests of Examples 1-3 and Comparative Examples 1-6 are as follows:
[0059] It can be seen from Comparative Examples 1-6 and Examples 1-3 that the relative density, tensile strength and wear rate of the products of the present invention can be improved in a coordinated manner. At the same time, when no modifying liquid or synergist is added to the product, the performance of the product deteriorates significantly. The performance effect of the product is most significant when the two are coordinated and work together. When no yttrium modifier is added to the modifying liquid, no treating agent is used in the preparation of the yttrium modifier, no lanthanum nitrate solution or dopamine hydrochloride solution is used in the treating agent, and no regulating liquid is used in the synergist, the performance of the product tends to deteriorate. Only when the product raw material obtained by the method of the present invention is used, the performance effect of the product is most significant.
[0060] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0061] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high-density tungsten-nickel-copper alloy material, characterized in that: The tungsten-nickel-copper alloy material includes tungsten, nickel, copper powder, modifying liquid and synergist; wherein the mass ratio of tungsten, nickel, copper powder, modifying liquid and synergist is (3-5): (1-3): (5-9): (12-14):
1.
2. A high-density tungsten-nickel-copper alloy material according to claim 1, characterized in that: The preparation method of the modified liquid is: S1: adding 2-4 parts of nano-silica sol and 1-3 parts of carboxymethyl cellulose to 4-7 parts of lanthanum nitrate solution, and then adding 1-2 parts of dopamine hydrochloride solution, stirring and mixing thoroughly to obtain a treating agent; S2: irradiating the yttrium oxide powder in a proton irradiation box, and obtaining irradiated yttrium oxide powder after the irradiation is completed; S3: stirring the irradiated yttrium oxide and the treatment agent in a weight ratio of 5:2 at a stirring speed of 300 r / min for 2 hours, washing with water and drying after the stirring is completed to obtain a yttrium modifier; S4: 2-4 parts of silane coupling agent KH560, 1-3 parts of urea, 2-5 parts of 6% by mass dodecylbenzenesulfonic acid solution and 2-5 parts of yttrium modifier are fully mixed to obtain a modified solution.
3. A high-density tungsten-nickel-copper alloy material according to claim 2, characterized in that: The mass fraction of the lanthanum nitrate solution is 2-5%; the mass fraction of the dopamine hydrochloride solution is 2-5%.
4. A high-density tungsten-nickel-copper alloy material according to claim 2, characterized in that: The irradiation power of the irradiation treatment is 350-400W, and the irradiation time is 20-30min.
5. The high-density tungsten-nickel-copper alloy material according to claim 1, characterized in that: The preparation method of the synergist is: S11: immersing the aluminum borate whisker into a sufficient amount of zinc sulfate solution, then washing and drying; S12: 2-4 parts of stearic acid, 1-3 parts of silane coupling agent KH550, 3-6 parts of sodium lignin sulfonate solution and 1-2 parts of nano-graphene are fully mixed to obtain a conditioning solution; S13: Stirring and adjusting the dried aluminum borate whiskers and the adjusting liquid in a weight ratio of 2:5, and after the stirring is completed, washing, filtering, and drying to obtain a synergist.
6. A high-density tungsten-nickel-copper alloy material according to claim 5, characterized in that: The mass fraction of the zinc sulfate solution is 5-8%; the mass fraction of the sodium lignin sulfonate solution is 6-9%.
7. The high-density tungsten-nickel-copper alloy material according to claim 5, characterized in that: The stirring temperature of the stirring adjustment treatment is 55-60° C., the stirring time is 35-45 min, and the stirring speed is 450-500 r / min.
8. The high-density tungsten-nickel-copper alloy material according to claim 5, characterized in that: The immersion power for full immersion is 350-400W, and the immersion time is 20-30min.
9. A method for manufacturing a high-density tungsten-nickel-copper alloy material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Tungsten, nickel, copper powder, modifying liquid and synergist are fully mixed, and then washed, filtered and dried to obtain a high-density tungsten-nickel-copper alloy material.